On Beckett : essays and criticism - Gontarski, S. E. (Anthem studies in theatre and performance., 2012)
"On Beckett: Essays and Criticism" is the first collection of writings about the Nobel Prize-winning author that covers the entire spectrum of his work, and also affords a rare glimpse of the private Beckett.